Risk of ischemic stroke and recurrent ICH in patients with atrial fibrillation presenting with incident ICH: an analysis from the Danish Stroke Registry. (25th November 2020) - Nielsen, P.B; Soegaard, M; Skjoeth, F; Larsen, T.B; Lip, G.Y.H
Abstract: Background: Intracerebral haemorrhage (ICH) is a devastating vascular event, and secondary prevention is central to avoid cerebral complications. The PRESTIGE-AF trial is a multinational randomized controlled trial designed to investigate the optimal stroke prevention strategy in atrial fibrillation (AF) patients who have suffered an ICH. Purpose: To examine one-year risk of cerebrovascular events in a study population similar to the expected PRESTIGE-AF trial. Methods: We used the Danish nationwide registries to identify all patients presenting with incident ICH and prevalent AF between 2003–2018. The study population was restricted using key inclusion criteria for trial participation: indication for antithrombotic treatment due to AF, and at least two CHA2DS2-VASc score stroke risk factors (three for females). Exclusion criteria were: ICH event occurring as a result of trauma or vascular malformation; other indication for long-term anticoagulant treatment; or use of left atrial appendage occlusion device. Patients were followed up in the Danish Stroke Registry, and outcomes were reported stratified by levels of the CHA2DS2-VASc score (score 2–3; 4–6; and >6 points). Results: A total of 16, 269 ICH patients were identified and after exclusions, 1797 patients were eligible for analysis. The main reason for exclusion was lack of AF diagnosis (81.2%). The study population mean age was 79.5 (SD: 8.7) and 48.1% were females. Among included patients 573 (%) had a CHA2DS2-VASc score of 2–3, 829 (%) had a score of 4–6, and 395 (%) had a score >6. The most prevalent stroke risk factors were hypertension (76.6%) and prior stroke (33.2%). During one-year follow-up, 56 ischemic stroke events and 43 recurrent ICH were observed at a rate of 4.33 (per 100 person-years) and 3.30, respectively. The Figure depicts risk development over time by means of cumulative incidence function based on the Aalen-Johansen estimator (factoring competing risk of death into the analytic approach). The risk of ischemic stroke was generally similar across strata of the stroke risk categories, while the risk of recurrent ICH was highest among patients with a CHA2DS2-VASc score >6 points. Conclusion: Using the Danish Stroke Registry, we identified a population mirroring the PRESTIGE-AF trial population. The patients were generally elderly and more than 68% had a CHA2DS2-VASc score of 4 or higher. The observed risk of ischemic stroke was similar across strata, while recurrent ICH was highest among those with a score >6 points. The outputs from the PRESTIGE-AF trial are warranted to determine optimal stroke prevention treatment patients with AF presenting with an ICH. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): This project has received funding from the European Union's Horizon 2020 research and innovation programme under grant agreement no. 754517